2020
DOI: 10.4048/jbc.2020.23.e53
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Updated Guidelines on Human Epidermal Growth Factor Receptor 2 (HER2) Testing in Breast Cancer

Abstract: Purpose In 2007, the American Society of Clinical Oncology and the College of American Pathologists had established a human epidermal growth factor receptor 2 (HER2) testing guideline, which was updated in 2013 and subsequently in 2018. We assessed the clinical impact of the recent update by comparing the in situ hybridization (ISH) results based on the 2007, 2013, and 2018 guidelines. Methods We assessed 2 cohorts. The first cohort included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…[18,19] Previous studies indicated that the positive and equivocal cases increased under the 2013 and 2018 guidelines. [20,21] In our study, the proportion of HER2 overexpressing in internal group was lower than external group (28.7% vs. 41.3%). In our study, the proportion of primary tumor response and axillary pCR in external cohort was higher than in retrospective series (34.5% vs. 24.5% and 29.9% vs. 16.1%, respectively).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…[18,19] Previous studies indicated that the positive and equivocal cases increased under the 2013 and 2018 guidelines. [20,21] In our study, the proportion of HER2 overexpressing in internal group was lower than external group (28.7% vs. 41.3%). In our study, the proportion of primary tumor response and axillary pCR in external cohort was higher than in retrospective series (34.5% vs. 24.5% and 29.9% vs. 16.1%, respectively).…”
Section: Discussioncontrasting
confidence: 52%
“…We suggested that it might be associated with the changing guideline of HER2 testing recommendation released in 2007, 2013, and 2018 by ASCO/CAP [18,19] . Previous studies indicated that the positive and equivocal cases increased under the 2013 and 2018 guidelines [20,21] . In our study, the proportion of HER2 overexpressing in internal group was lower than external group (28.7% vs .…”
Section: Discussionmentioning
confidence: 50%